Pengaruh Pengetahuan Kesehatan dan Keselamatan Kerja (K3) terhadap Efikasi Diri Siswa pada Pelajaran Instalasi Penerangan Listrik - Syaputra, Yori Afrian; Mukhaiyar, Riki (Jurnal Pendidikan Teknik Elektro, 2024)
This study aims to describe and analyze the readiness of K3 knowledge on self-efficacy of students of the Electric Power Installation Engineering Expertise Program of SMK Negeri 1 Pariaman. K3 knowledge readiness is an overall individual condition that includes physical, mental, and experiential life and the willingness and ability to carry out work or an activity. The research method used in this research is descriptive and quantitative. The variable studied was the readiness of K3 knowledge of students in the Electric Power Installation Engineering expertise program of SMK Negeri 1 Pariaman. The research instrument used in this study is a questionnaire distributed directly to respondents with 1 variable and 7 indicators. This research questionnaire was conducted on class XI Electrical Power Installation Engineering students totaling 25 respondents. The data analysis technique in this study is descriptive percentage statistics. The results of this study can be concluded that the readiness of K3 knowledge of students of the Electrical Power Installation Engineering expertise program of SMK Negeri 1 Pariaman, some are ready to work and some are continuing their higher education or entrepreneurship.